2010
DOI: 10.3109/03091902.2010.497892
|View full text |Cite
|
Sign up to set email alerts
|

Are Doppler studies a useful method of assessing neovascularization in human Achilles tendinopathy? A systematic review and suggestions for optimizing machine settings

Abstract: Achilles tendinopathy describes a painful condition. The symptoms include localized swelling and tenderness, and the condition is often associated with altered tendon structure and neovascularization. Doppler ultrasound has been used in Achilles neovascularization and despite the lack of standardization and machine settings, recent research has demonstrated a potential relationship between pathology and the presence of neovascularization. This paper is a systematic review of the published studies which have us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 53 publications
4
41
0
Order By: Relevance
“…However, we are confident that our conservative findings did not result from decreased ultrasound sensitivity, as we used a lower pulse-repetition frequency setting compared to that used by Walther et al 23 (781 versus 1102 Hz), which improved sensitivity to lowfrequency shift. 25 Consistent with the findings of a systematic review investigating diagnostic imaging for plantar fasciitis, 16 our findings show greater plantar fascia thickness in participants with plantar fasciitis compared to controls, and a strong association between plantar fascia thickness greater than 4.0 mm and heel pain. However, further exploration of our data revealed that 9 controls had plantar fascia thickness greater than 4.0 mm, and of these, 7 had a BMI of 30 kg/m 2 or greater.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, we are confident that our conservative findings did not result from decreased ultrasound sensitivity, as we used a lower pulse-repetition frequency setting compared to that used by Walther et al 23 (781 versus 1102 Hz), which improved sensitivity to lowfrequency shift. 25 Consistent with the findings of a systematic review investigating diagnostic imaging for plantar fasciitis, 16 our findings show greater plantar fascia thickness in participants with plantar fasciitis compared to controls, and a strong association between plantar fascia thickness greater than 4.0 mm and heel pain. However, further exploration of our data revealed that 9 controls had plantar fascia thickness greater than 4.0 mm, and of these, 7 had a BMI of 30 kg/m 2 or greater.…”
Section: Discussionsupporting
confidence: 89%
“…PDU settings were standardized with a pulse-repetition frequency of 781 Hz, although 5 participants were assessed with a higher pulse-repetition frequency (977 Hz) to reduce flash artifact. 25 Doppler gain was optimized by manual elevation until the first indication of color (representing background noise) began to appear at the calcaneal enthesis or proximal plantar fascia. 23 The sonographers were aware of clinical history (ie, plantar fasciitis or not) during assessments.…”
mentioning
confidence: 99%
“…In the light of recent well-performed research, it seems that detecting neovessels has no additional value for the diagnosis, no firmly confirmed prognostic value, and no proven relation with symptoms [33]. Also, all these issues lack of standardization of machine settings before expanding on the role of the neovascularization itself in the process of tendinopathy [52]. Hence, as Holmes said before, it should be clear that 'It is a capital mistake to theorize before one has data.…”
Section: The Achilles Heelmentioning
confidence: 99%
“…Some previous studies have suggested that neovascularization contributes to painful Achilles tendinopathy. Previous studies have described sclerosing neovessels in order to relieve pain in most patients [7]. One study found that higher levels of glutamate receptors and vascular endothelial growth factors exist in the vicinity of the nerves in patients with painful Achilles tendinopathy, suggesting that the increase in nociceptive nerve fibers and neovascularization occurs in Achilles tendinopathy [8].…”
Section: Introductionmentioning
confidence: 99%